Overview and Challenges of Large-Scale Cultivation of Photosynthetic Microalgae and Cyanobacteria - Novoveská, Lucie; Nielsen, Søren Laurentius; Eroldoğan, Orhan Tufan; Haznedaroglu, Berat Zeki; Rinkevich, Baruch; Fazi, Stefano; Robbens, Johan; Vasquez Christodoulou, Marlen; Einarsson, Hjörleifur (My University, 2023)
Microalgae and cyanobacteria are diverse groups of organisms with great potential to benefit societies across the world. These organisms are currently used in food, feed, pharmaceutical and cosmetic industries. In addition, a variety of novel compounds are being isolated. Commercial production of photosynthetic microalgae and cyanobacteria requires cultivation on a large scale with high throughput. However, scaling up production from lab-based systems to large-scale systems is a complex and potentially costly endeavor. In this review, we summarise all aspects of large-scale cultivation, including aims of cultivation, species selection, types of cultivation (ponds, photobioreactors, and biofilms), water and nutrient sources, temperature, light and mixing, monitoring, contamination, harvesting strategies, and potential environmental risks. Importantly, we also present practical recommendations and discuss challenges of profitable large-scale systems associated with economical design, effective operation and maintenance, automation, and shortage of experienced phycologists.
Keywords: cyanobacteria cultivation; large-scale cultivation; microalgae cultivation; scale-up